1986
DOI: 10.1128/aac.30.5.684
|View full text |Cite
|
Sign up to set email alerts
|

Multiply resistant mutants of Enterobacter cloacae selected by beta-lactam antibiotics

Abstract: Mutants of Enterobacter cloacae, selected in vitro with ceftriaxone, ceftazidime, carumonam, or aztreonam, fell into several distinct classes. Three mutants highly resistant to nearly all beta-lactam antibiotics were stably derepressed for beta-lactamase production. Although no other changes could be detected, virulence in a mouse septicemia model was decreased in two of these mutants. One mutant, 908-Ssi, showed selectively decreased susceptibility to ampicillin and cefotetan. A change in beta-lactamase expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
2
16
2
Order By: Relevance
“…These results may seem unexpected because other researchers previously reported that the MIC of imipenem either did not change (1,4,6,30) or increased only slightly (25) in porin-deficient mutants of enteric bacteria. However, in contrast to our strains, all of the strains used in these earlier studies produced 3-lactamase at much lower levels: the activities measured by using 0.…”
Section: Resultscontrasting
confidence: 48%
“…These results may seem unexpected because other researchers previously reported that the MIC of imipenem either did not change (1,4,6,30) or increased only slightly (25) in porin-deficient mutants of enteric bacteria. However, in contrast to our strains, all of the strains used in these earlier studies produced 3-lactamase at much lower levels: the activities measured by using 0.…”
Section: Resultscontrasting
confidence: 48%
“…Various data do not favor this hypothesis. First, E. cloacae 908S (the wild-type ␤-lactamaseinducible strain) and E. cloacae 908R (the ␤-lactamase-overproducing strain) show the same level of resistance to various non-␤-lactam antibiotics such as chloramphenicol, norfloxacin, nalidixic acid, or erythromycin, and these levels are the same as those observed for Salmonella wild-type strains (24,31). Moreover, the P for benzylpenicillin, a ␤-lactam sensitive to efflux systems, is the same for E. aerogenes 006, the wild-type strain, and E. aerogenes 008-4.…”
Section: Discussionmentioning
confidence: 59%
“…Minimum inhibitory concentrations (MIC) for antibiotics were determined by agar dilution on Mueller Hinton Agar [9].…”
Section: Methodsmentioning
confidence: 99%